The Migration Period between the Oder and the Vistula (2 vols)
1 online resource.
Keywords: This collection of studies is the result of a six-year interdisciplinary research project undertaken by an international team of archaeologists, historians, numismatists and paleobotanists. It constitutes a completely new approach to environmental, cultural and settlement changes during the Migration Period in Central Europe. Part One discusses written sources, theories regarding migration, and environmental change in the first millennium AD. In Part Two, archaeological sources relating to Central Europe in the Migration Period are analysed, while Part Three is devoted to new discoveries between the Oder and the Vistula, including traces of Germanic settlement in northern Poland in the early seventh century. In Part Four, evidence for cultural and settlement changes in neighbouring areas is characterized in a comparative light.